3-D VISUALIZATION: VOLCANIC HAZARD MAPS EDUCATE PEOPLE EXPOSED TO VOLCANIC RISK - Villegas, Henry (Geoambiente On-line, 2013)
Since the most reliable volcanic hazard map will be of little use unless it is presented in a meaningful format, the Volcanic Hazard Map of Nevado del Huila Volcano (Colombia) was combined with remote sensing data and visualized in 3-D. This visualization methodology could be used with any volcanic hazard map available, in order to generate products that could help improving the communication between volcanologists and people not familiar with volcanoes. The right understanding of any volcanic hazardous situation will avoid or minimize damaging consequences to people exposed to such natural risk.Volcanoes with their eruptions and other related hazards had lo <!-- @page { margin: 2cm } P { margin-bottom: 0.21cm } -->